Re-establishing Apoptosis Competence in Bone Associated Cancers via Communicative Reprogramming Induced Through Notch Signaling Inhibition - Colombo, Michela; Platonova, Natalia; Giannandrea, Domenica; Palano, Maria Teresa; Basile, Andrea; Chiaramonte, Raffaella (Frontiers in Pharmacology, 2019)
Notch and its ligands on adjacent cells are key mediators of cellular communication during developmental choice in embryonic and adult tissues. This communication is frequently altered in the pathological interaction between cancer cells and healthy cells of the microenvironment due to the aberrant expression of tumor derived Notch receptors or ligands, that results in homotypic or heterotypic Notch signaling activation in tumor cells or surrounding stromal cells. A deadly consequence of this pathological communication is pharmacological resistance that results in patient’s relapse. We will provide a survey of the role of Notch signaling in the bone marrow (BM), a microenvironment with a very high capacity to support several types of cancer, including primary cancers such as osteosarcoma or multiple myeloma and bone metastases from carcinomas. Moreover, in the BM niche several hematological malignancies maintain a reservoir of cancer stem cells, characterized by higher intrinsic drug resistance. Cell-cell communication in BM-tumor interaction triggers signaling pathways by direct contact and paracrine communication through soluble growth factors or extracellular vesicles, which can deliver specific molecules such as mRNAs, miRNAs, proteins, metabolites, etc. enabling tumor cells to reprogram the healthy cells of the microenvironment inducing them to support tumor growth. In this review we will explore how the dysregulated Notch activity contributes to tumor-mediated reprogramming of the BM niche and drug resistance, strengthening the rationale of a Notch-directed therapy to re-establish apoptosis competence in cancer.